Kilka uwag o problemach dowodowych w procesach o czyny z art. 256 k.k. - Paluszkiewicz, Hanna; Jasińska, Marta (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The way in which a given conduct is normatively framed and the extent to which it is criminalized has a direct impact on the possibility of initiating and conducting criminal proceedings for the offence. The analysis of new types of offences related to the propagation of the Nazi and communist system and the punishment of the public propagation of Nazi, communist and fascist ideology, as well as the public propagation of an ideology inciting the use of violence with the aim of influencing political or social life into Article 256 of the Penal Code leads to the conclusion that, contrary to the intentions of the legislator, the amendment of the provision in question will not facilitate the prosecution of the perpetrators of such acts. What is more, the fact that a provision of a criminal law with vaguely formulated elements remains in legal circulation directly affects the possibility of establishing a factual basis in the case for the initiation of criminal proceedings, the bringing of charges, the prosecution and trial of the perpetrator of such acts.
Keywords: totalitaryzm; postępowanie karne; postępowanie dowodowe; nieokreśloność znamion czynu zabronionego